Targeting the cancer-neuronal crosstalk in the pancreatic cancer microenvironment - Capodanno, Ylenia; Hirth, Michael (International journal of molecular sciences, 2023)
Pancreatic ductal adenocarcinoma (PDAC) represents one of the most aggressive solid tumors with a dismal prognosis and an increasing incidence. At the time of diagnosis, more than 85% of patients are in an unresectable stage. For these patients, chemotherapy can prolong survival by only a few months. Unfortunately, in recent decades, no groundbreaking therapies have emerged for PDAC, thus raising the question of how to identify novel therapeutic druggable targets to improve prognosis. Recently, the tumor microenvironment and especially its neural component has gained increasing interest in the pancreatic cancer field. A histological hallmark of PDAC is perineural invasion (PNI), whereby cancer cells invade surrounding nerves, providing an alternative route for metastatic spread. The extent of PNI has been positively correlated with early tumor recurrence and reduced overall survival. Multiple studies have shown that mechanisms involved in PNI are also involved in tumor spread and pain generation. Targeting these pathways has shown promising results in alleviating pain and reducing PNI in preclinical models. In this review, we will describe the mechanisms and future treatment strategies to target this mutually trophic interaction between cancer cells to open novel avenues for the treatment of patients diagnosed with PDAC.